Safety, pharmacokinetics, and immunogenicity of a co-formulated cocktail of three human monoclonal antibodies targeting Ebola virus glycoprotein in healthy adults: a randomised, first-in-human phase 1 study. Issue 8 (August 2018) - Sivapalasingam, Sumathi; Kamal, Mohamed; Slim, Rabih; Hosain, Romana; Shao, Weiping; Stoltz, Randall; Yen, Joseph; Pologe, Laura G; Cao, Yuan; Partridge, Michael; Sumner, Giane; Lipsich, Leah
Summary: Background: REGN3470-3471-3479 is a co-formulated cocktail of three human monoclonal antibodies targeting three non-overlapping epitopes on Ebola virus. We investigated safety, tolerability, pharmacokinetics, and anti-drug antibodies in healthy adults. Methods: This randomised, double-blind, placebo-controlled, dose-escalation study was done at a phase 1 unit in the USA. Healthy adults, aged 18–60 years, with a body-mass index of 18·0–30·0 kg/m 2 were randomly assigned (3:1) to receive a single intravenous dose of REGN3470-3471-3479 or placebo on day 1 (baseline) in one of the four sequential ascending intravenous dose cohorts (3 mg/kg, 15 mg/kg, 60 mg/kg, and 150 mg/kg). Site investigators and participants were masked to the treatment assignment, whereas designated personnel at the site who prepared and generated the study medication were aware of the randomisation treatment assignments. The primary outcome was safety and the secondary outcomes were the pharmacokinetic profiles and immunogenicity. Study assessments were done the day before study drug administration, on the day of drug administration, on day 2 (before discharge), on days 3, 4, 8, 15, 29, 57, 85, 113, and 141, and at the end of study on day 169. The safety analysis included all randomised participants who received study drug. This trial is registered with ClinicalTrials.gov, number NCT002777151 . Findings: Between May 18, 2016, and October 27, 2016, 70 adults were screened and 24 participants were enrolled in the study. 18 participants were assigned to and received REGN3470-3471-3479, and six participants were assigned to and received placebo as a single intravenous infusion. 19 treatment-emergent adverse events occurred in the combined REGN3470-3471-3479 treatment groups, and four treatment-emergent adverse events occurred in combined placebo groups. Adverse events were transient and mild-to-moderate in severity. The most common treatment-emergent adverse event was headache (six [33%] of 18 participants in the combined REGN3470-3471-3479 group vs none of six participants in the placebo group. Headaches were mild-to-moderate in severity, with onset between 2 h and 27 days after start of study drug infusion. There were no deaths, serious adverse events, or adverse events that led to study discontinuation. The pharmacokinetics of each antibody was linear, with mean half-lives of 27·3 days for REGN3471, 21·7 days for REGN3470, and 23·3 days for REGN3479. No participants tested positive for anti-REGN3470, anti-REGN3471, or anti-REGN3479 antibodies. Interpretation: REGN3470-3471-3479 was well tolerated, displayed linear pharmacokinetics, and did not lead to detectable immunogenicity. These data support further clinical development of REGN3470-3471-3479 as a single-dose therapeutic drug for acute Ebola virus infection. Funding: The Department of Health and Human Services, the Office of the Assistant Secretary for Preparedness and Response, and the Biomedical Advanced Research and Development Authority.